2017
DOI: 10.3945/ajcn.117.156380
|View full text |Cite
|
Sign up to set email alerts
|

Time of day and eating behaviors are associated with the composition and function of the human gastrointestinal microbiota

Abstract: Preclinical research has shown that the gastrointestinal microbiota exhibits circadian rhythms and that the timing of food consumption can affect the composition and function of gut microbes. However, there is a dearth of knowledge on these relations in humans. We aimed to determine whether human gastrointestinal microbes and bacterial metabolites were associated with time of day or behavioral factors, including eating frequency, percentage of energy consumed early in the day, and overnight-fast duration. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
95
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(105 citation statements)
references
References 50 publications
5
95
1
4
Order By: Relevance
“…Therefore, this observation in the gut microbiota under LE conditions may suggest a potential proinflammatory profile and a higher risk of intestinal inflammatory‐related diseases with LE in fecal microbiota. Along those lines, a recent observational study has reported significant associations between the relative abundance of several gut bacterial families and the distribution of energy intake before or after 1400 h (25). Nevertheless, further food timing interventional studies in obese and diabetic subjects are needed to confirm these results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this observation in the gut microbiota under LE conditions may suggest a potential proinflammatory profile and a higher risk of intestinal inflammatory‐related diseases with LE in fecal microbiota. Along those lines, a recent observational study has reported significant associations between the relative abundance of several gut bacterial families and the distribution of energy intake before or after 1400 h (25). Nevertheless, further food timing interventional studies in obese and diabetic subjects are needed to confirm these results.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of timing of food intake on microbiota in humans has not been investigated. However, studies in rodents on feeding patterns (23), in equines on feeding frequency (24) and in humans on daily energy intake distribution and gut microbial abundances (25) have provided compelling evidence to support the hypothesis that several aspects related to the time of eating can affect microbiota and could be one of the mechanisms for late‐eating—induced metabolic dysfunction.…”
mentioning
confidence: 99%
“…TRF on weekdays has been shown to restrict weight gain in HFD-fed juvenile male rats (between 5 and 13 wk of age) independently of caloric intake (47). TRF is associated with increased production of SCFAs, specifically acetate, propionate, and butyrate (34). TRF also restores normal circadian cycling within the microbiota composition, characterized by an increase in Firmicutes abundance during the day and a decrease during the night (67).…”
Section: Eating Patternsmentioning
confidence: 99%
“…In contrast to studies in mouse models, clinical studies investigating diurnal fluctuations in gut microbiota remain scarce . In particular, these observations are from small subject cohorts and rely only on limited time points.…”
Section: Diurnal Oscillations In Microbiotamentioning
confidence: 99%